Scope and limitations of the protected designation of origin for mezcal in Mexico. - Salinas García, Esteban; Alcaraz Vera, Jorge Víctor; Durán Tovar, Edith Sarai; Chávez Rivera, Rubén (Agricultura, Sociedad y Desarrollo, 2023)
To the extent that mezcal is commercialized, the micro, small, and medium businesses (MIPYMES for initials in Spanish) that produce this artisanal product, linked to diverse and heterogeneous practices that are more sustainable, are systematically and legitimately excluded from the management of plantations and agaves and the knowledge to elaborate the product under the Designation of Origin for Mezcal (DOM). It favors industrial production focused on capital accumulation and which responds to the demand, particularly of the international market. This designation of origin reflects the political and legal schemes that the Mexican State uses to legitimize the exclusion and transition from artisanal production to an industrialized production process. The objective of this essay, is to contribute to the discussion about the scope and limitations of the distinction-protected designation of Origin (PDO), whether it is a benefit or a detriment since although some states and regions belong to the designation, they do not show growth and much less local development. In any case, the benefits are obtained by brokers and promoters of the designation, with which they acquire the product at a low price and trade it in the international market at a higher price, transferring the economic benefits to other regions of the country.